Leadership and Governance: A Case of Cattle Rustling as a Security Threat in Nigeria - Mohammed Bashir Abubakar (Rechtsidee, 2019)
Since the beginning of this political dispensation, Nigeria has suffered a lot from bad leadership with most of its leaders not concentrating on the welfare and security of its citizens because of corruption. Poor leadership undermines the legitimacy of democratic values and tolerance from the leaders and other stakeholders. However, the link between leadership and security challenges in Nigeria was analysed. Qualitative method of data collection was adopted, and secondary data was used. The paper found that cattle rustling as a security threat Nigeria was a product of bad leadership in Nigeria. The paper concludes that, until good leadership devoid of corruption, religious and ethnic interest is put in place, transparency and accountability in all aspect of governance is maintained, cattle rustling will be the order of the day.